Detrital zircon provenance and palaeogeographic implications of the Ediacaran Shigu Group in the Zhongza Terrane, SW China. Issue 17 (21st November 2020) - Su, Bingrui; Cui, Xiaozhuang; Tian, Jingchun; Lai, Chun Kit; Ren, Fei; Ren, Guangming; Liu, Shilei
ABSTRACT: The palaeogeographic positions of South China in the Rodinia and Gondwana supercontinents have long been controversial. We report petrological, detrital zircon U-Pb geochronological, trace element geochemical and Lu-Hf isotopic compositions for metasedimentary rocks from the Shigu Group in the Zhongza Terrane, SW China. The Shigu Group has been regarded as the Precambrian basement of the Zhongza Terrane, and comprises mainly a suite of medium-/low-grade metamorphosed terrigenous clastic rocks. The youngest zircon age population of two metasedimentary rock samples from the bottom Shigu Group yields a weighted average age of 633 ± 9 Ma, indicative of a late Neoproterozoic (ca. 630 Ma) maximum deposition age. The youngest detrital zircon age of a metasedimentary rock from the upper Shigu Group is 597 ± 7 Ma, it may suggesting a considerably later deposition. Detrital zircon age distribution patterns of the Shigu Group metasedimentary rocks are similar to those of coeval sedimentary rocks in the western Yangtze Block. According to Hf isotope compositions and zircon morphology, the Neoproterozoic Shigu Group detritus may have sourced from Neoproterozoic magmatic rocks in the western Yangtze Block, whilst the pre-Neoproterozoic zircons might originate from recycling of the underlying metasedimentary rocks. Our results indicate that the basement of the Zhongza Terrane was a continuation of the Yangtze Block, which implies that Precambrian Yangtze basement rocks were present beyond the current boundary of the Block. In the late Neoproterozoic (ca. 630–570 Ma), the western Yangtze Block may have been facing the Proto-Tethys and received detritus mainly from the local Neoproterozoic magmatic rocks. During the late Neoproterozoic-earliest Palaeozoic (ca. 570–520 Ma), the seaway closure between the Yangtze (incl. Zhongza) Block and northern India likely created new pathways for delivery of the earliest Neoproterozoic and Pan-African detrital zircons into the lowermost Palaeozoic sequences in South China.